Archetypal Coaching - Carod, Alba (Taylor & Francis, 2026)
Archetypal Coaching offers a transformative approach to personal growth, blending ancient Greek astrological foundations and dream work with modern coaching techniques, somatic awareness, and Jungian active imagination. Astrological archetypes illuminate the roots of struggles and highlight potential resources, while dreams act as a focused lens, bringing attention to issues that require immediate exploration. The approach explored within this book emphasizes interactive dialogue with archetypes and symbols, using embodied imagination and somatic awareness to guide clients in creating a personal symbol that embodies their inner process and potential, echoing Jung’s concept of the transcendent function. Supported by six in-depth case studies and numerous examples, the author outlines a holistic framework for integrating astrology and dream work into coaching, emphasizing personal growth and treating archetypes as dynamic tools for creativity and self-discovery. This book will appeal to established coaches, counselors, and therapists interested in integrating archetypal work into their practice, as well as students of Jungian psychology, coaching, art therapy, astrology, and related fields.